Strategies for spatial analysis of carbon emissions from human-social systems: A framework based on energy consumption and land use - Wang, Chenxing; Wang, Zetong; Zheng, Lifu; Lu, Shifang; Li, Xiaoyun; Rong, Yuejing; Shang, Xu; Song, Wentao; Zhang, Jing; Yan, Yan (Frontiers in Ecology and Evolution, 2022)
As cities are the main source of carbon emissions for human-social systems, clarifying the characteristics of carbon emission structure and distribution in urban areas is an important foundation for achieving carbon neutrality of cities, and also an important challenge for human-social systems to achieve global carbon balance goals. The spatial utilization of cities is often characterized by the agglomeration of construction land, population concentration and industrial production, with high carbon emission intensity and large total amount. The current research on the quantification of regional carbon emissions is mainly in two categories: bottom-up calculation method system based on emission inventory and top-down method system based on energy balance and input-output model. However, how to clarify both the total regional carbon emissions and their spatial distribution has been a difficult problem in the field of carbon emission quantification. Based on the comprehensive consideration of these two aspects, this study tried to construct an approach that combines the top-down carbon emission measurement method with the bottom-up spatialization process. The total carbon emissions of the human-society system are specified to each land patch, and thereby the carbon emission pattern of each emission sector in the city could be determined. In this study, we quantified the carbon emissions of Nanjing in 2020 and obtained the spatial pattern of carbon emissions in this city based on land use. The results showed that the carbon emission intensity of the main urban area of Nanjing was much higher than that of other districts, while energy consumption of the industrial production system was the main source of carbon emissions in the human-social system there. The method of this study has a relatively wide applicability and can help researchers and the governments to clarify the quantity and location of their carbon emissions clearly, which is meaningful for the implementation of urban carbon reduction strategies.